»Nærvær« in absentia: At opleve performance som dokumentation - Jones, Amelia; Daugaard, Solveig (Peripeti, 2024)
Focusing specifically on body art, art historian Amelia Jones questions the »ontology of presence« which informs much performance art and theory. Jones claims that a differentiated reception must involve the immediate performance experience as well as different forms of documentation and historical contextualisation.